LUKAY ART IN CEBU: A HERITAGE OF LIVING TRADITIONS - Reynaldo B. Inocian (European Scientific Journal, ESJ, 2013)
This study is a documentary analysis of “puso” (rice-pouch/hanging rice) used as a ritual object among the village farmers in Taptap, an isolated mountain barangay of Cebu City. “Puso” is an embodiment of the cultural identity of the Cebuanos that needs ardent preservation as a heritage of living traditions. The use of ethnography and actual observation revealed that “puso” is used in the farm rituals. Six major designs of “puso” were documented as the last few pieces of the elaborate designs woven before the 13th century prior to the arrival of the Spaniards in 1521. Actual weaving and cooking processes were photographed, art elements and principles were analyzed in each design, and symbolisms were identified based on the actual ritual. All these variables were juxtaposed to establish a need for preservation. The cultural preservation of intangible heritage is an advantage for successful socio-cultural-tourism framework.